2019
DOI: 10.1038/s41431-019-0341-5
|View full text |Cite
|
Sign up to set email alerts
|

Breakpoint mapping at nucleotide resolution in X-autosome balanced translocations associated with clinical phenotypes

Abstract: Precise breakpoint mapping of balanced chromosomal rearrangements is crucial to identify disease etiology. Ten female patients with X-autosome balanced translocations associated with phenotypic alterations were evaluated, by mapping and sequencing their breakpoints. The rearrangements' impact on the expression of disrupted genes, and inferred mechanisms of formation in each case were assessed. For four patients that presented one of the chromosomal breaks in heterochromatic and highly repetitive segments, we c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…NHEJ is considered the major mechanism responsible for the formation of balanced chromosomal alterations [ 20 , 47 ]. Moysés-Oliveira et al [ 20 ] reported mutational signatures of c-NHEJ in the breakpoints of six out of ten patients in a study of X-autosome balanced translocations.…”
Section: Mechanisms Of Structural Chromosomal Rearrangement Formationmentioning
confidence: 99%
“…NHEJ is considered the major mechanism responsible for the formation of balanced chromosomal alterations [ 20 , 47 ]. Moysés-Oliveira et al [ 20 ] reported mutational signatures of c-NHEJ in the breakpoints of six out of ten patients in a study of X-autosome balanced translocations.…”
Section: Mechanisms Of Structural Chromosomal Rearrangement Formationmentioning
confidence: 99%
“…Prenatal FISH Weise and Liehr (2008) For limitations of FISH in general, there are to mention, that 1) the resolution in standard FISH is limited to kilo-to megabasepair (except for molecular combing approach), and thus exact mapping of chromosomal breakpoints needs combined approaches like, e.g., applied in Jancuskova et al (2013) or Moysés-Oliveira et al (2019), 2) disease causing gene mutations at base pair level normally cannot be accessed by FISH-one exception was recently published (Molecular Combing Section) (Nguyen et al, 2019), 3) as in cytogenetics and next-generation sequencing (NGS) for qualified evaluation and interpretation of FISH-results experienced specialists are needed, 4) corresponding to question to be studied costs of consumables may be relatively high, and 5) number of probes being applied simultaneously is limited by number of fluorochromes and software; however, recent developments proved also solutions for this (Su et al, 2020).…”
Section: Routine Diagnostics Referencesmentioning
confidence: 99%
“…The evolution of accurate and affordable next-generation sequencing (NGS) techniques, such as whole genome sequencing (WGS), has been fundamental to elucidate breakpoints at nucleotide resolution contrib-uting to a molecular diagnosis [Aristidou et al, 2017[Aristidou et al, , 2018Schluth-Bolard et al, 2019]. Low coverage WGS, for example, is an efficient method for the detection and characterization of balanced translocations [Liang et al, 2017], and this characterization is improved when WGS is combined with cytogenomic methods [Moysés-Oliveira et al, 2019]. A more cost-effective strategy corresponds to the sequencing of specific microdissected segments from the derivative chromosomes, targeting the genomic regions surrounding the breakpoints [Jancuskova et al, 2013].…”
Section: © 2020 S Karger Ag Baselmentioning
confidence: 99%
“…cDNA samples were assayed in technical triplicate with standard PCR conditions of the 96-Well Fast Thermal Cycling (Thermo Fisher Scientific) and Applied Biosystems 7900HT Sequence Detection System (Thermo Fisher Scientific). A qualitative analysis was performed to assess the relative gene expression between the proband and controls as previously described [Moysés-Oliveira et al, 2019].…”
Section: Quantitative Rt-pcrmentioning
confidence: 99%